Supplementary Table S1 from In Vivo Screening Unveils Pervasive RNA-Binding Protein Dependencies in Leukemic Stem Cells and Identifies ELAVL1 as a Therapeutic Target - Ana Vujovic (15207479) (2025)
Table S1 shows expression of RBPs in an RNA-sequencing data set of human bone marrow hematopoietic stem and progenitor subpopulations.